Bone health and exercise throughout the lifespan - Stuhr, Robyn; American College of Sports Medicine; Monterey Bay Video Production Co.; Insight Media ([Indianapolis, In.] : Monterey Bay Video Production Co. [production] ; New York : Insight Media [distributor], 2006)
Reviews why exercising to develop and maintain healthy bones is important at all stages of life and how to design a population-specific exercise program to enhance bone health
Title from title screen
Keywords: Exercise therapy -- Management; Exercise therapy -- Management; Exercise therapy; Physical fitness; Bones